2018
DOI: 10.1038/s12276-018-0113-2
|View full text |Cite
|
Sign up to set email alerts
|

Lactate potentiates angiogenesis and neurogenesis in experimental intracerebral hemorrhage

Abstract: Lactate accumulation has been observed in the brain with intracerebral hemorrhage (ICH). However, the outcome of lactate accumulation has not been well characterized. Here, we report that lactate accumulation contributes to angiogenesis and neurogenesis in ICH. In the first set of the experiment,  a rat model of ICH was induced by injecting collagenase into the brain. The effects of lactate accumulation on the neurological function, apoptosis, and numbers of newborn endothelial cells and neurons, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…Lactate accumulation was associated with intracerebral hemorrhage, and it has been verified with the in vivo MRS method. However, there are only a few studies that discuss the function of lactate accumulation 12 . Lactate accumulation has been verified as contributing to angiogenesis and neurogenesis in ICH model, 12 which could interpret partial self‐healing after hemorrhages, especially in the penumbra area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lactate accumulation was associated with intracerebral hemorrhage, and it has been verified with the in vivo MRS method. However, there are only a few studies that discuss the function of lactate accumulation 12 . Lactate accumulation has been verified as contributing to angiogenesis and neurogenesis in ICH model, 12 which could interpret partial self‐healing after hemorrhages, especially in the penumbra area.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are only a few studies that discuss the function of lactate accumulation 12 . Lactate accumulation has been verified as contributing to angiogenesis and neurogenesis in ICH model, 12 which could interpret partial self‐healing after hemorrhages, especially in the penumbra area. Furthermore, we hypothesized that lactate accumulation could facilitate the migration and proliferation of the microglia cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rat model of ICH induced by a collagenase injection, new neurons migrated from the SVZ to the lesion, increasing the regeneration of nerves in the white matter. In addition, an exogenous lactic acid injection after ICH increased the transcription of VEGF and basic fibroblast growth factor (BFGF) through the translocation of nuclear factor‐kappa B (NF‐kappa B), which plays an active role in angiogenesis and neurogenesis . Otero L et al showed that ICH induced strong endogenous neurogenesis within 72 hours to 7 days after injury, but most of the new cells survived less than 3 weeks due to apoptotic‐mediated apoptosis .…”
Section: Repair or Recovery Mechanism And Strategymentioning
confidence: 99%
“…(NF-kappa B), which plays an active role in angiogenesis and neurogenesis. 61 Otero L et al showed that ICH induced strong endogenous neurogenesis within 72 hours to 7 days after injury, but most of the new cells survived less than 3 weeks due to apoptotic-mediated apoptosis. 62 In addition, neurogenesis continued in a small range for at least 1 year after ICH, which provides us with a novel view that promoting endogenous nerve regeneration can improve the prognosis of patients with hemorrhagic stroke.…”
Section: Neurogenesismentioning
confidence: 99%